2009
DOI: 10.1016/j.jss.2009.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Alters the Hepatic Inflammatory Cellular Profile Without Changes in Matrix Degradation During Liver Repair Following Biliary Decompression

Abstract: Background Biliary atresia is characterized by extrahepatic bile duct obliteration along with persistent intrahepatic portal inflammation. Steroids are standard in the treatment of cholangitis following the Kasai portoenterostomy and were liberally adopted advocated for continued suppression of the ongoing immunological attack against intrahepatic ducts. Recent reports however have failed to demonstrate an improved patient outcome or difference in the need for liver transplant in postoperative patients treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
(27 reference statements)
2
6
0
Order By: Relevance
“…The strong association between prednisone treatment and protein metabolism may also contribute to the changes in the urinary proteome. Several differential proteins identified in current study were reported to be regulated by glucocorticoids in previous studies, such as the serine protease inhibitor A3N, 12 alpha-1-acid glycoprotein, 13 mMP8, 14 growth hormone receptor 15 insulin-like growth factor-binding protein 3 16 and acyl-CoA-binding protein, 17 suggesting the reliability of the proteomics results. Moreover, two differentially expressed proteins (Haptoglobin and Neutrophil collagenase) in our study were further validated by Western Blot.…”
Section: Discussionsupporting
confidence: 70%
“…The strong association between prednisone treatment and protein metabolism may also contribute to the changes in the urinary proteome. Several differential proteins identified in current study were reported to be regulated by glucocorticoids in previous studies, such as the serine protease inhibitor A3N, 12 alpha-1-acid glycoprotein, 13 mMP8, 14 growth hormone receptor 15 insulin-like growth factor-binding protein 3 16 and acyl-CoA-binding protein, 17 suggesting the reliability of the proteomics results. Moreover, two differentially expressed proteins (Haptoglobin and Neutrophil collagenase) in our study were further validated by Western Blot.…”
Section: Discussionsupporting
confidence: 70%
“…Muratore et al have provided the explanation that dexamethasone can alter the hepatic inflammatory cellular profile without changes in matrix degradation during liver repair following biliary decompression [39]. Previous studies by the authors have demonstrated that glucocorticoid treatment suppresses LPSinduced chemokine expression and inflammatory cells infiltration as well as oxidative stress in cholestatic rats receiving biliary intervention [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…In the first few weeks of life, a Kasai portoenterostomy is performed to bypass the obstructed extrahepatic bile ducts and restore the biliary flow. 3 Approximately 20% of all patients who undergo portoenterostomy during infancy survive into adulthood with their native liver. 2 , 4 In general, it is advantageous to perform portoenterostomy as early after birth as possible to optimize the chance of success.…”
mentioning
confidence: 99%